Effect of Ultrafine Bubble Additives on the Properties of B-35 Diesel Fuel - Husen Asbanu; Sam Herodian; Tineke Mandang; Anto Tri Sugiarto; Riesta Anggarani (The University of Lampung, 2025)
Improving the quality of B-35 biodiesel fuel is crucial, especially in distillation and flash point parameters that affect performance and safety. The objective of this study was to analyze the effect of oxygen ultrafine bubble application on the fuel characteristics of B-35 including cetane number, viscosity, density, flash point, distillation, and cloud point. Tests were conducted according to ASTM standards: D86 (distillation), D93A (flash point), D613 (cetane number), D445 (viscosity), D4052 (density), and D5773 (cloud point). The treatment was performed by injecting oxygen ultrafine bubble at a rate of 1, 3, and 5 l/min into 1.5 liters of fuel for 10–60 minutes. The results showed the highest distillation temperature of 339.7 °C at 1 l/min and 10 minutes, while the lowest temperature of 330.9 °C was achieved at 5 L/min and 60 minutes (control: 341.6 °C). The highest flash point of 72 °C occurred in the low oxygen injection rate and short duration, while the lowest was 64.5 °C in the high rate and long duration. The treatment increased cetane number from 58.6 to 60.8. The decrease in viscosity and density was insignificant but remained within standard limits. The cloud point decreased from 7.1 °C to 5 °C. UFB oxygen addition shows significant potential in improving the quality and combustion efficiency of B-35 fuel